Synergistic Opportunities for Computational Resource Providers and Local IT - Gray, Zane (My University, 2014)
Talk Abstract How do high-speed data paths benefit research computing, and should you care? This talk explores the means of engaging local Information Technology resources to build two-way, collaborative partnerships that enable the achievement of research goals. We will discuss examples of how this relationship benefits local IT through exposure to cutting edge technologies prior to introduction into the campus or enterprise environment — a selling point in an affiliation that has traditionally been more "take" than "give." We will also discuss when circuit services, Science DMZ's, and Research and Education Networks are appropriate enough to warrant engagement with local or regional IT resources.
Biography Zane Gray is the Data and Telecommunications Manager for the University of Oklahoma's Norman Campus. He received his Bachelor of Science in Chemical Engineering from OU in 1996. Before returning to OU as a network engineer, he was employed as a civilian with the United States Air Force, and deployed computer networks throughout the United States. At OU, he collaborates with a team of highly talented network associates; oversees the daily operations and maintenance of the campus computer network; charts the direction of a network design that supports tens of thousands of devices; interacts with other IT professionals, faculty, and students; and faces the day to day challenges of change with a smile.
Keywords: Computer Science